Hubungan Life Goes On: Pengalaman Resiliensi pada Individu yang Pernah Melakukan Percobaan Bunuh Diri - Sania Utami Putri; Mario Pratama (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Suicide attempts are a complex mental health issue with long-term psychological implications, particularly regarding an individual’s ability to adaptively rebuild their life. This study aims to understand experiences of resilience among individuals who have attempted suicide. The method used is a qualitative approach with an interpretive phenomenological design, involving three participants selected through purposive sampling based on specific criteria. Data were collected through in-depth interviews, observation, and triangulation with supporting informants, then analyzed using Interpretative Phenomenological Analysis (IPA). The results indicate that resilience is formed through a dynamic process encompassing phases of a crisis of meaning, reconstruction of self-identity, and the strengthening of protective factors such as social support, adaptive coping mechanisms, and life meaning. Furthermore, temporal factors play a crucial role in stabilizing participants’ psychological conditions. These findings affirm that resilience is a multidimensional process that develops gradually through the interaction between an individual’s subjective experiences and social context.